2015
DOI: 10.1111/jrh.12105
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Utilization of Health Care Services for Rural VA Enrollees With Mental Health‐Related Diagnoses

Abstract: Based on these variations, the VA may want to develop strategies to increase screening efforts in inpatient settings and emergency rooms to further capture rural VA enrollees who have undiagnosed mental health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Andersen’s health behavioral model is the cornerstone of many studies assessing patient healthcare-seeking behavior and the accessibility of health services. The model has been used to improve healthcare services worldwide [11, 12, 23]. Our results demonstrated that there were significant demographic/pregnancy and environmental factor differences among pregnant women attending primary, secondary and tertiary hospitals.…”
Section: Discussionmentioning
confidence: 79%
“…Andersen’s health behavioral model is the cornerstone of many studies assessing patient healthcare-seeking behavior and the accessibility of health services. The model has been used to improve healthcare services worldwide [11, 12, 23]. Our results demonstrated that there were significant demographic/pregnancy and environmental factor differences among pregnant women attending primary, secondary and tertiary hospitals.…”
Section: Discussionmentioning
confidence: 79%
“…However, this study revealed having a mental health condition, including suicide attempts or self-harm, as a reason for emergent ED use. This association may be a reflection of access to mental healthcare, which has been shown to be hindered by distance to a provider, geography, and provider shortages, especially in rural areas [ 46 , 54 ]. Mental health patients potentially not having access to a primary-care provider or mental health specialist could result in not having the necessary resources available for regular treatment and, therefore, not seeking care until it is of emergent level in order to avoid costs they cannot afford.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the ‘any chronic disease/illness’ variable was recorded as ‘absence of a chronic disease/illness’. The ‘admission mental health’ variable equaled ‘presented due to mental health disease/illness’ if the admission diagnosis field contained an ICD-9 code for depression, anxiety, post-traumatic stress, schizophrenia, suicide, self-harm, or alcohol or substance abuse [ 5 , 21 , 26 , 46 ]. Otherwise the ‘admission mental health’ variable equaled ‘did not present due to mental health disease/illness’.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to these reports, another study based on VHA data found that rural enrollees with mental health diagnoses were more likely than urban VA enrollees to have a mental health contact in an inpatient, office-based, or emergency room setting (Johnson et al, 2015) and a study of VHA service users who had served in Iraq found that rural veterans were more likely to receive diagnoses of PTSD and to receive treatment for PTSD and depression than their urban counterparts (Hudson et al, 2014). Finally, according to a national VHA analysis from 2014, while only 23.9% of all veterans live in rural areas, 32.9% of VA enrollees come from rural areas, suggesting that rural veterans are more likely to enroll in VHA services than urban veterans (Cowper Ripley et al, 2015).…”
mentioning
confidence: 95%
“…Military veterans are of particular concern in these areas because the all-volunteer U.S. military recruits more extensively from rural than urban areas, many veterans return home after their service, and suicide rates are elevated among veterans, as they are among non-veterans, in rural areas (Finn, 2006; Hammil, 2005; Kane, 2005; McCarthy et al, 2012). According to the Office of Rural Health of the Veterans Health Administration (VHA), 4.7 million veterans, about one-fourth of the total, live in non-urban areas (Office of Rural Health, 2019) and are thought to be at increased risk for mental health problems due to higher rates of poverty, greater distances to VHA facilities, reduced access to transportation, limited housing opportunities, and greater mental health stigma (Johnson et al, 2015; Office of Rural Health, 2019). Some studies suggest that even when rural veterans have similar or lower rates of mental health and substance use conditions, they report lower physical and mental health-related quality-of-life as compared to their urban counterparts (Wallace et al, 2006).…”
mentioning
confidence: 99%